2019
DOI: 10.1093/nar/gkz186
|View full text |Cite
|
Sign up to set email alerts
|

The RecQ helicase Sgs1 drives ATP-dependent disruption of Rad51 filaments

Abstract: DNA helicases of the RecQ family are conserved among the three domains of life and play essential roles in genome maintenance. Mutations in several human RecQ helicases lead to diseases that are marked by cancer predisposition. The Saccharomyces cerevisiae RecQ helicase Sgs1 is orthologous to human BLM, defects in which cause the cancer-prone Bloom's Syndrome. Here, we use single–molecule imaging to provide a quantitative mechanistic understanding of Sgs1 activities on single stranded DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
(116 reference statements)
0
30
0
Order By: Relevance
“…On the other hand, a recent in vitro study found that similar to Srs2, Sgs1 can dismantle Rad51 filaments, albeit with some mechanistic differences. Sgs1 was able to translocate on RPA-coated ssDNA without dislodging RPA, but stripped off Rad51 [152]. In contrast to Srs2, which strips off RPA and Rad51 by stimulating Rad51 ATP hydrolysis activity, there was no difference in the ability of Sgs1 to dislodge ATPase-deficient or ATPase-proficient Rad51 from ssDNA [152,153].…”
Section: Roles Of Sgs1 In Dsb Repairmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, a recent in vitro study found that similar to Srs2, Sgs1 can dismantle Rad51 filaments, albeit with some mechanistic differences. Sgs1 was able to translocate on RPA-coated ssDNA without dislodging RPA, but stripped off Rad51 [152]. In contrast to Srs2, which strips off RPA and Rad51 by stimulating Rad51 ATP hydrolysis activity, there was no difference in the ability of Sgs1 to dislodge ATPase-deficient or ATPase-proficient Rad51 from ssDNA [152,153].…”
Section: Roles Of Sgs1 In Dsb Repairmentioning
confidence: 89%
“…Sgs1 was able to translocate on RPA-coated ssDNA without dislodging RPA, but stripped off Rad51 [152]. In contrast to Srs2, which strips off RPA and Rad51 by stimulating Rad51 ATP hydrolysis activity, there was no difference in the ability of Sgs1 to dislodge ATPase-deficient or ATPase-proficient Rad51 from ssDNA [152,153]. This Sgs1 activity may be used to prevent the formation of deleterious HR intermediates at stalled replication forks, to disrupt heteroduplexes, or to displace the invading Rad51 filament in D-loops, thereby channeling HR intermediates into the synthesis-dependent strand annealing (SDSA) pathway of DSB repair that produces noncrossover products [152,[154][155][156].…”
Section: Roles Of Sgs1 In Dsb Repairmentioning
confidence: 99%
“…This is consistent with the observation that replication forks in rrm3 mutants also stall at Fob1-independent sites. Other DNA helicases, such as Sgs1 and Srs2, which are also capable of removing DNA-bound proteins [21,22], were dispensable for replication through RFB [20]. This raises the possibility that the factors that promote fork escape in rrm3 tof1 and rrm3 csm3 mutants may not be another DNA helicase, but could involve DNA motor proteins that remodel DNA or chromatin.…”
Section: Replication Through the Rdna Replication Fork Barriermentioning
confidence: 99%
“…On the other hand, the STR complex, via Top3 decatenation activity, is capable of dismantling D-loops in vivo, favoring the formation of NCOs by the SDSA repair pathway both in the meiotic [76,77] and mitotic [13] programs ( Figure 1). Although in vitro assays using artificial D-loops suggested that Top3 preferentially dismantles protein-free D-loops [78,79], more recent single-molecule imaging analysis has revealed that Sgs1 possesses the ability to disrupt Rad51-bound ssDNA nucleofilaments [80]. Like Srs2 [50,53], Sgs1 cannot act on Dmc1-coated ssDNA filaments, but unlike Srs2, the mechanism employed by the Sgs1 helicase to remove Rad51 is independent of the Rad51 ATPase cycle [80].…”
Section: The Dissolvase Role Of the Multifaceted Str Complexmentioning
confidence: 99%
“…Although in vitro assays using artificial D-loops suggested that Top3 preferentially dismantles protein-free D-loops [78,79], more recent single-molecule imaging analysis has revealed that Sgs1 possesses the ability to disrupt Rad51-bound ssDNA nucleofilaments [80]. Like Srs2 [50,53], Sgs1 cannot act on Dmc1-coated ssDNA filaments, but unlike Srs2, the mechanism employed by the Sgs1 helicase to remove Rad51 is independent of the Rad51 ATPase cycle [80]. Top3-Rmi1 can also dissolve Rad51-mediated D-loops via a topoisomerase-dependent mechanism without the participation of the Sgs1 helicase [78].…”
Section: The Dissolvase Role Of the Multifaceted Str Complexmentioning
confidence: 99%